The concepts of menopause. Part I – demographical and cultural approach - Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2005)
Menopause is most often approached from the biomedical perspective. Such a perspective was also popular in the past. Nowadays new approaches to menopause emerge and psychological as well as cultural aspects are also considered. The first part of the paper describes views presented in the 19th century medical literature. What follows is the analysis of menopause from the demographic perspective. The effects of growing numbers of women in postmenopausal age are discussed. The last part of the paper deals with cultural aspects of menopausal transition. The role of culture in developing attitudes toward menopause is discussed and areas of cultural differences in menopausal symptoms, knowledge about transition and coping are presented.